EVALUATION OF BACTERIAL QUALITY OF GOAT’S MILK IN DUHOK PROVINCE - MOHAMMED, ISSA M.; SULAIVANY, JWAN K. M. AL-; AYED, MAHMOUD A. (Journal of Duhok University, 2021)
A total of 102 samples of native goat’s milk and local Maraz goat milk were collected from the district of Summel in Duhok governorate from various farms for the period of February, 1 up to 1 May, 2016. The aim of this study was to evaluate both types of milk bacteriologically. The results showed that Native goat or black goat milk samples were contaminated with different strains of bacteria; pollution percentages for the total bacterial count, Enterobacteriaceae and Staphylococcus aureus were (41.17, 13.72 and 21.56 %), respectively; and the same bacteria as averages were (24x107, 5.17 x 104 and 4.18x103 CFU/ml) respectively. The results of Maraz milk showed that the pollution percentages for the total of bacterial count, Enterobacteriaceae and Staphylococcus aureus were (45.09, 13.72 and 15.68%), respectively; and as average were (21.7x107, 3.4x104 and 4.1x103 CFU/ml), respectively; while there were no Salmonella bacteria presence in the studied milk samples of both local and Maraz goats. While there were different strains of Enterobacteriaceae bacteria (42.85 % of E. coli I, 14.28 % of E. coli II, 7.14 % of K. pneumonia, 14.28 % of K Pneumoniae II, 7.14 % of type K. oxtoca and 14.28 % belong to type Shigella sp). The results of Staphylococcus aureus showed that they produce plasma coagulation enzyme as 100 %, catalase enzyme as 63.15 %, lecithinase as 84.21 %, gelatinase as 73.68 % and enzyme alpha amylase as 89.47%. In conclusion all studied samples of milk were free of Salmonella, but some studied samples contained strains of Enterobacteriaceae that is a bad indicator on the human, due to make illness.